Zircon recycling and crystallization during formation of chromite- and Ni-arsenide ores in the subcontinental lithospheric mantle (Serranía de Ronda, Spain) - González-Jiménez, J.; Marchesi, C.; Griffin, W.; Gervilla, F.; Belousova, E.; Garrido, C.; Romero, R.; Talavera, Cristina; Leisen, M.; O'Reilly, S.; Barra, F.; Martin, L. (Elsevier Science BV, 2017)
The ultramafic massifs of the Serranía de Ronda (namely Ronda, Ojén and Carratraca) are portions of Proterozoic (~1.2-1.8Ga) subcontinental lithospheric mantle (SCLM) affected by partial melting and infiltration of melts. The latter of these events was broadly coeval with the tectonic emplacement of the peridotites into the continental crust in the Early Miocene. This resulted in the formation of chromite and Ni-arsenide ores (Cr-Ni) associated with orthopyroxenites and cordieritites. Six zircons recovered from a massive chromitite sample from the Ronda massif yield both concordant and discordant ages between 2309±37Ma and 109±15Ma, and d18O between 8.3‰ and 9.4‰. Two Proterozoic ages obtained for zircons of this population (1815±9Ma and 1794±17Ma) are identical, within error, to those of zircons reported previously in the garnet pyroxenites of Ronda (1783±37Ma). Similarly, concordant Early Jurassic (192±13Ma) and Cretaceous ages (109±15Ma) obtained from the core and rim, respectively, of a single zircon from the chromitite are also consistent with the ages (180±5Ma, 178±6Ma, and 131±3Ma) already reported for magmatic zircons from corunudum-bearing garnet pyroxenites in the Ronda massif. The observation that chromitites and garnet-pyroxenites contain similar populations of zircons suggests that the parental melts of chromitites inherited zircons from their protolithic garnet pyroxenites, representing relics of oceanic/arc crust recycled in the mantle. Eleven zircons recovered from a massive cordieritite associated with chromitite in the Ronda massif yield scattered concordant and discordant ages between 568Ma and 21Ma, with correspondingly variable d18O (4.8-13.5‰) and unradiogenic Hf-isotope ratios (eHf(t) from -12.36 to -4.43). The youngest age is concordant at 21.18±0.4Ma and matches the ages of zircons from the chromitite (weighted average age of 20.4±0.87Ma, n=4) and a plagioclasite dyke (scattering between 20.1±0.2Ma and 17.9±0.1Ma; n=11) associated with the Cr-Ni mineralization in the Ojén massif. These zircons show similar unradiogenic Hf-(eHf(t) between -14.5 and -7.6) and heavy O-isotope compositions (d18O=11.3-12.4‰). A sample of the massive cordieritite hosting the chromitites contains abundant zircons that yield scattered concordant, sub-concordant and discordant U-Pb ages varying from 33.8±1Ma to 781±10Ma; these zircons (n=21) have variable U-contents (105-13900ppm) and Th/U ratios (0.003-0.8). On the basis of O- and Hf-isotope compositions, these zircons define three populations independently of their ages: (1) grains with consistent high d18O (6.1-12.7‰) and negative eHf(t) (from -14.42 to -6.88); (2) grains with high d18O (7.6-11.1‰) and positive eHf(t) (3.10-4.84); and (3) grains with d18O<5.5‰ typical of mantle values. We suggest that zircons from this cordieritite with U-Pb ages older than Miocene are inherited, and were incorporated physically into the SCLM by fluids or melts produced during dehydration-melting of the crustal rocks wrapping the peridotite massifs. The population of Early Miocene zircons found in the chromitites and associated cordieritites and the plagioclasite dyke in the mineralization of the Ojén massif date the crustal emplacement of the peridotites and, therefore, the formation of the Cr-Ni ores. We propose a model in which the unique Cr-Ni mineralizations found in the ultramafic rocks of the Serranía de Ronda were formed as a result of contamination of the SCLM with crustal components.